In Vitro protein digestibility and fermentability of mulberry (Morus alba)-Leucaena foliage mixed feed - Dwi Yulistiani; Z. A. Jelan; J. B. Liang (Indonesian Center for Animal Research and Development (ICARD), 2016)
This experiment was carried out to determine the effect of mulberry-leucaena foliage mixed feed on protein digestibility and VFA production using an in vitro gas production study. Mulberry was mixed with one of 2 leucaena varieties (Leucaena leucocephala hybrid and Leucaena leucocephala local) at 3 levels (0, 25 and 50%). Study was conducted in completely randomized design. Mulberry foliage, leucaena and mixtures of mulberry-leucaena were incubated for 24 hours in glass syringes. Parameter recorded were gas production, in vitro true dry matter digestibility (IVTDMD), in vitro N digestibility (IVND) and VFA production. Results of the study showed that supplementation of leucaena to mulberry decreased IVOMD, gas production and protein digestibility in the rumen buffered medium. The mixture of mulberry and leucaena hybrid at ratio 50% resulted in the lowest IVND than other treatment. However it increased protein digestibility in acid pepsin incubation as an estimate of protein availability in intestine. Gas production decreased in mulberry leucaena mixtures was followed by decreased total VFA production. Tannin derived from leucaena hybrid supplementation to mulberry at ratio 1 : 1 was most effective to decrease protein digestion in the rumen and to increase protein digestibility in acid pepsin incubation. In conclusion mixing of hybrid leucaena hybrid with mulberry foliage was able to protect protein degradation from mulberry in the rumen.